THE UTILIZATION OF FLASHCARD AND GROUP ACTIVITY THERAPY ON EDUCATION RELATED TO THE DASH KNOWLEDGE AMONG HEALTH CADRES - Mazarina Devi, Hilda; Sulistiawati, Dewi; Putri, Rona Sari Mahaji (Indonesian Journal of Community Health Nursing, 2025)
Objective: Analyzing the influence of Dietary Approaches to Stop Hypertension (DASH) education using flashcard media and group activity therapy on the level of knowledge of integrated health post or Posyandu (Pos Kesehatan Terpadu) cadres in Banjarejo Village, Ngantang District, Malang Regency, East Java Province, Indonesia. Design: The pre-experimental with pretest-posttest used as research design. Setting: The research was elaborated at Banjarejo Village Sport Center, Ngantang District, Malang Regency, East Java, Indonesia. Data collection on June 2024. Method: The population was 63 health cadres from five Posyandu, selected using purposive sampling with a sample size of 42 people. The DASH knowledge questionnaire used as instrument with parameters Understanding DASH, Objectives, Types, Examples of types of food, Principles of the DASH diet, how to process food, benefits of the DASH diet, Composition, examples of processed foods DASH Diet and the concept of the DASH diet. Flashcard and interactive games used in the process of data collection. Data analysis used the marginal homogeneity test. Result: The results showed that before being given education about DASH with flashcard media, most of the Posyandu cadres had knowledge in the poor category (57.1%) and after being given education, the knowledge of Posyandu cadres was in the good category (52.4%). The results of the marginal homogeneity test obtained a p value = 0.001 (<0.05). Conclusion: There is an influence of DASH education with flashcard media and group activity therapy on the level of knowledge of health cadres in Banjarejo Village, Ngantang District, Malang Regency. This research not only provides significant scientific contributions on knowledge, but also has a positive impact in increasing empowerment capacity to maintain the health of population against hypertension. Keywords: DASH, empowerment, flashcard media, group therapy, hypertension, knowledge.